Health and flood: hidden dangers and challenges of flood disaster - Aung, Khin Thandar; Nurumal, Mohd. Said; Ahayalimudin, Nurul‘Ain; Abdul Rahman, Nurul 'Inayati (Scholars Academic and Scientific Publisher, 2018)
Floods are the most common natural disaster and the highest fatality rate among the natural disaster around the world. The health impacts of floods are wide ranging, and depend on many factors. The physical and mental health may be affected during and after flooding. With that, it is important to be aware that the impact on health due to floods and there is needed to implement a comprehensive management in preparedness, response and recovery phase of flood disaster management to reduce the adverse effects of floods as well as for the ffectiveness of public health intervention. The purpose of this paper was to illustrate the health impacts of floods and to explore the hidden dangers and challenges during and aftermath of flood disaster. The reviewed literature for this paper was based on the related data sources of floods,flooding, disasters, extreme events, health impacts, floods and health, health impacts of flood in PubMed, Google scholar and research gate within fifteen years. In this paper, the health impacts due to flooding from different dimensions such as impacts of physical health and mental health have been discussed and then explored the hidden dangers and challenges during and aftermath of the flood disaster. During the flood and its aftermath, there are also threats to an individual’s health and safety. It is strongly suggested that enhanced public health planning and interventions could focus on the precise practices and mechanisms that intersect to produce anxiety, stress, and their amelioration at individual and community levels.